The Relationship between Active Trachoma and Ocular Chlamydia trachomatis Infection before and after Mass Antibiotic Treatment. - Athumani M Ramadhani; Tamsyn Derrick; David Macleod; Martin J Holland; Matthew J Burton (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Trachoma is a blinding disease, initiated in early childhood by repeated conjunctival infection with the obligate intracellular bacterium Chlamydia trachomatis. The population prevalence of the clinical signs of active trachoma; ''follicular conjunctivitis" (TF) and/or ''intense papillary inflammation" (TI), guide programmatic decisions regarding the initiation and cessation of mass drug administration (MDA). However, the persistence of TF following resolution of infection at both the individual and population level raises concerns over the suitability of this clinical sign as a marker for C. trachomatis infection. METHODOLOGY/PRINCIPLE FINDINGS:We systematically reviewed the literature for population-based studies and those including randomly selected individuals, which reported the prevalence of the clinical signs of active trachoma and ocular C. trachomatis infection by nucleic acid amplification test. We performed a meta-analysis to assess the relationship between active trachoma and C. trachomatis infection before and after MDA. TF and C. trachomatis infection were strongly correlated prior to MDA (r = 0.92, 95%CI 0.83 to 0.96, p<0.0001); the relationship was similar when the analysis was limited to children. A moderate correlation was found between TI and prevalence of infection. Following MDA, the relationship between TF and infection prevalence was weaker (r = 0.60, 95%CI 0.25 to 0.81, p = 0.003) and there was no correlation between TI and C. trachomatis infection. CONCLUSIONS/SIGNIFICANCE:Prior to MDA, TF is a good indicator of the community prevalence of C. trachomatis infection. Following MDA, the prevalence of TF tends to overestimate the underlying infection prevalence. In order to prevent unnecessary additional rounds of MDA and to accurately ascertain when elimination goals have been reached, a cost-effective test for C. trachomatis that can be administered in low-resource settings remains desirable.